Understanding factors that influence at-risk student perceptions of teaching and learning environments at university - Jere, Joseph Ntabeni (African Perspectives of Research in Teaching and Learning Journal (APORTAL), 2026)
This study examines factors influencing at-risk students’ perceptions of teaching and learning at a South African university. Using the Experiences of Teaching and Learning Questionnaire (ETLQ), data were collected from 631 undergraduate students identified as at risk of not completing their degree programmes within the stipulated minimum periods. Structural equation modelling was used to test a theorised model of factors associated with student perceptions. The findings suggest that the perceptions of at-risk students regarding teaching and learning environments are significantly related to assessment practices and degree programme demands. However, there was insufficient evidence to support associations between student perceptions and organisation and structure, teaching and learning approaches, or lecturer support. The initially theorised model showed a poor fit, necessitating the development of a revised model. These findings underscore the importance of considering assessment design and programme workload when developing teaching and learning interventions for at-risk students. This study contributes to research on enhanced teaching and learning environments by applying the ETLQ in a different cultural context, offering insights for improving educational quality in higher education settings
Journal article published in African Perspectives of Research in Teaching and Learning Journal Volume 10, Issue 1, 2026
Keywords: Constructive alignment; ETLQ; Structural equation modelling; Student perceptions; Teaching and learning; Education higher; Mainstreaming in education; College students; College teaching